Are the Dixit-Pindyck and the Arrow-Fisher-Henry-Hanemann Option Values Equivalent? - Iulie Aslaksen; Terje Synnestvedt (Statistics Norway, Research Department, 2004)
The relationship between the concept of option value in the literature on environmental preservation and the financial theory of option value is discussed by Fisher (2000), suggesting an equivalence between the two concepts. In a recent paper, Mensink and Requate (2004) argue that Fisher's claim is incorrect. In this paper we clarify Fisher's argument by drawing on the article by Hanemann (1989), whereby we find the conditions for the Arrow-Fisher-Henry-Hanemann (AFHH) and the Dixit-Pindyck (DP) option value concepts to coincide or not. The main point is that the AFHH option value is derived under the assumption that investment does not take place in the first period, neither in the closed-loop nor in the open-loop strategy, whereas the analysis of the DP option value is based on the assumption that investment in the open-loop strategy takes place in the first period.
Keywords: D81; Q20; 330; Option value; Uncertainty; Information; Irreversibility; Environment